AZD5153 reverses palbociclib resistance in ovarian cancer by inhibiting cell cycle-related proteins and the MAPK/PI3K-AKT pathway. (1st March 2022) - Liu, Chen; Huang, Yuhan; Qin, Tianyu; You, Lixin; Lu, Funian; Hu, Dianxing; Xiao, Rourou; Qin, Xu; Guo, Ensong; Yang, Bin; Li, Xi; Fan, Junpeng; et al.
Abstract: The CDK4/6 inhibitor, palbociclib has recently entered clinic-trial stage for breast cancer treatment. However, translating its efficacy to other solid tumors has been challenging, especially for aggressive solid tumors. We found that the effect of palbociclib as a single agent was limited due to primary and acquired resistance in multiple ovarian cancer (OC) models. Among these, patient-derived organoid and xenograft models are two most representative models of drug responsiveness in patients with OC. In preclinical models, this study demonstrated that activated MAPK/PI3K-AKT pathway and cell cycle-related proteins induced the resistance to palbociclib, which was overcome by the addition of the bromodomain protein 4 (BRD4) inhibitor AZD5153. Moreover, this study revealed that AZD5153 and palbociclib had a synergistic lethal effect on inducing the cell cycle arrest and increasing apoptosis, even in RB-deficient cell lines. Based on these results, it is anticipated that this class of drugs, including AZD5153, which inhibit the cell cycle-related protein and MAPK/PI3K-AKT pathway, will exhibit synergistic effects with palbociclib in OC. Highlights: We established four preclinical drug screening models, 2D/3D cell lines, PDO and PDX model in ovarian cancer. AZD5153 reversed palbociclib resistance by inhibiting cell cycle-related proteins and MAPK/PI3K-AKT pathway. AZD5153 and palbociclib have a synergistic lethal effect on inducing the cell cycle arrest and increasing apoptosis, even in RB-deficient cell lines.